Evaluation of the kitchen microbiome and food safety behaviors of predominantly low-income families - Carstens, Christina K.; Salazar, Joelle K.; Sharma, Shreela V.; Chan, Wenyaw; Darkoh, Charles (Frontiers in Microbiology, 2022)
Bacterial pathogens in the domestic environment present a risk to residents, particularly to susceptible populations. However, the impact of consumer demographic characteristics and food handling methods on kitchen microbiomes is not fully understood. The domestic kitchen bacterial communities of ten predominantly low-income families in Houston, Texas, was assessed in conjunction with a cross-sectional food safety survey to evaluate differences in household and surface-specific microbiomes and bacterial foodborne pathogen presence. Three kitchen surfaces within each household, including the sink drain, the refrigerator handle, and the counter, were environmentally sampled and metataxonomically evaluated via targeted 16S rRNA sequencing. Disposable dish sponges were also acquired and examined. Results indicated significant differences in beta diversity among the bacterial communities of five pairs of households and between refrigerator handle and disposable dish sponge microbiomes. A total of 89 unique bacterial foodborne pathogens were identified across surface types. Each household contained at least one contaminated surface, and the most common bacterial foodborne pathogens identified were Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae. All participants reported washing their hands before meal preparation, fresh fruits and vegetables, and cutting boards with soap after use to prepare raw animal proteins. Gaps in food safety behaviors identified included a lack of serious concern for food contamination with germs and improper hand washing, food handling, and cleaning behaviors. The number of unique bacterial foodborne pathogens identified within households was significantly higher among households that did not consider food contamination with germs to be a serious food safety problem (median: 41.0 species) compared to households that thought food contamination to be a serious food safety problem (median: 3.0 species; p-value = 0.0218). These results demonstrate that domestic kitchen taxonomic abundance profiles vary according to households and surface type. The data suggests that low-income consumers may be at risk of foodborne pathogen exposure from contaminated home kitchen surfaces. That food safety attitudes may directly contribute to this hazard.